DAMPAK PENGGUNAAN ALAT DAN MESIN PERTANIAN TERHADAP BIAYA PRODUKSI PADI DI DESA PAKATELLU KECAMATAN KUSAN HILIR KABUPATEN TANAH BUMBU - MARIA ULFAH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Maria Ulfah (2018) This research entitled " The Impact of Agricultural Machinery And Means On The Cost Of Rice Production in Pakatellu Village, Kusan Hilir Subdistrict, Tanah Bumbu Regency". Under the guidance Dra. Hj. Ika Chandriyanti, MP.               This study want to find out the impact of use tools and agricultural machinery on rice production and rice production costs in Pakatellu Village. The analytical method used is Paired sample t-test. The respondents were 75 farmers, determined by simple random sampling. Data processed using SPSS 23.               The results indicate there is a change of rice yields before and after using agricultural tools and machinery, and there is a reduction in the cost of wage for planting and harvesting labor because using tools and machinery. Therefore, author suggest for farmers in Pakatellu and in other villages that if there are still those who have not used agricultural tools and machinery to apply them. Keywords: Agricultural Equipment and Machinery; Rice Production; Production Cost